Er friheden taget ud af friskolen? - Olsen, Tore Vincents (Politik, 2014)
The article investigates the last 15 years’ changes in the Danish law regarding private schools and asks to what extent the ideological and pedagogical freedom of the private schools have become more restricted. It traces the changes back to general concerns with integration of cultural and religious minorities and with the academic quality of schools, the latter in light of the international competitiveness of Danish society. e article nds that the freedom of the schools has become more limited and discusses whether the e orts to limit their freedom go beyond what is legitimate from a liberal democratic point of view. e article nds that it is legitimate for a liberal democratic state to presuppose ability for political autonomy among its citizens, but it is controversial for the state to demand that schools instill speci c values and loyalties into their students.